Wave‐influenced deposition of carbonate‐rich sediment on the insular shelf of Santa Maria Island, Azores. Issue 4 (13th January 2022) - Zhao, Zhongwei; Mitchell, Neil C.; Quartau, Rui; Moreira, Sandra; Rusu, Liliana; Melo, Carlos S.; Ávila, Sérgio P.; Das, Diya; Afonso, Pedro; Pombo, Joaquim; Duarte, João; Rodrigues, Aurora
Abstract: Formulae for sediment thresholds of motion are commonly based on flume experiments on rounded quartz particles and it is unclear how well they predict thresholds in natural settings. Here, sediment threshold shear stresses were calculated from one such formula using surface grain‐size data from 112 sites around Santa Maria Island, Azores. To compare with those stresses, a Simulating Waves Nearshore model was run for three typical winter months to predict shelf stress maxima due to waves. As wind‐driven and other circulations also increase stresses, the model predictions are under‐estimates. Comparison of the two stress estimates suggests that the whole shelf of the island was mobile during extreme conditions. However, three forms of evidence contradict this. First, 129 rollovers of sandy clinoforms lying in 30 to 200 m water depths around the island were identified from boomer seismic data. It has been suggested that such rollovers mark depths at which hydrodynamic stresses fall beneath the sediment threshold of motion. Second, differences in grain‐size diversity between carbonate‐free and whole sediment indicate where carbonate particle fragmentation occurs. Third, seabed images reveal variations in ripple character and presence. The combined data suggest that deposition has occurred in the middle and outer shelf, overlapping where the model predicts sediment mobilization. However, by decreasing the model bottom shear stress or increasing the shear stress at threshold of motion by a factor of two to three, deposition is predicted to have occurred immediately deeper than the shallow active rollovers. Therefore, in practice, the ratio of wave‐imposed shear stress to stress at threshold of motion is two to three times smaller than predicted. This is speculated to be due to the presence of widespread hard substrates and other features shielding particles between them from wave stresses. Alternatively, the threshold of motion is higher than expected from the formulae for these sediments dominated by bioclastic particles.